PERSEPSI CALON PELAMAR KERJA TERHADAP TEMPAT KERJA IDEAL STUDI KASUS MAHASISWA TINGKAT AKHIR UNIVERSITAS DI INDONESIA - Prabowo, Sakti (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2017)
Perception Research of Talent to Ideal Workplace Case Study of Final-Year University in Indonesia aims to describe the dominant factors behind the career choice of students and to know the level of student interest for a career in the Ministry of Finance. Respondent surveys are final-year university students, consist of 20 best universities in Indonesia and 5 (five) Universities that manifest affirmative action program as representative from outside East Java / Indonesia. Based on the results, the perception of talent on the selection of the ideal place of work according to the respondent is a company / organization that provides high income, good career opportunities and a comfortable working environment. 80,7% of respondents stated their approval that the Ministry of Finance has a positive image as an ideal workplace according to respondents' choice. Meanwhile, in the competition of the national job market, the Ministry of Finance is ranked second place where the worker is considered ideal and desired by the respondents, under PT Pertamina which is ranked number one.